Linguistic landscape study: signs of public transportation places in Sidoarjo regency - Putra, Valdi Giffari Rahmayati; Novela, Fanda; Busri, Hasan (Universitas Mulawarman, 2024)
This study focuses on the linguistic landscape in public transportation places in Sidoarjo Regency. It aims to analyze the use and function of language on signs at Sidoarjo Train Station, Waru Train Station, Purabaya Bus Station, Larangan Bus Station, and Juanda Airport. According to Spolsky and Cooper's theoretical framework, signs are classified based on various criteria forming language taxonomy on signs. The data collection was conducted using observation and interviews. The interview was conducted with one person (passenger) at each location and the observation lasted for four days for all locations, followed by data integration and analysis. The study identified 94 signs, including 62 monolingual (Indonesian and English) and 32 bilingual (Indonesian-English) signs functioning as prohibition, warning, labeling, direction, and information. The findings found the diverse linguistic landscape in the public transportation places in Sidoarjo Regency, which had an impact on communication and navigation for both domestic and foreign passengers. Furthermore, for future research, the researchers suggest using mixed methods for analysis and addressing specific areas, particularly enhancing the clarity and visibility of prohibition signs for passenger safety.